2nd draft report of CARICOM regional civil society consultation, Trinidad and Tobago (CPDC BridgetownBB, 2011)
Discusses the Draft Regional Strategic Framework (RSF) which emerged from Phase 1, a data gathering round of national consultations held in each of the 15 CARICOM Member States.
Keywords: CIVIL SOCIETY